THE PEOPLE’S KNOWLEDGE AND INTENTION IN USING ONLINE PSYCHOLOGICAL INTERVENTIONS - Raudhoh, Siti; Iranda, Agung; Annisa, Verdiantika; Rahman, Marlita Andhika (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background The development of telepsychology in Indonesia is inseparable from the impacts of the Covid-19 pandemic. One of its manifestations is online-based psychological interventions. With numerous growing applications in Indonesia, most of these services only provide counseling via chat with a psychologist. Indeed, the forms of online-based psychological interventions are not limited to chat. Further identifications are required to see if these online-based psychological interventions appeal to the community. This study aims to depict the knowledge and intention of the community to use online psychological interventions and the correlation between them. Method This study was quantitative research with survey method. The number of involved respondents was 127 male and female respondents aged 17-40. Result Research results show that 39.37% of respondents fell into the moderate category of knowledge, 22.04% fell into the low category, and 26.77% fell into the high category. About 49.61% of respondents indicated moderate intention, and 22.83% indicated a reasonably high intention to use online psychological interventions should they face mental health issues. Online interventions perceived as appealing for the community should they experience mental health issues were web-based intervention, psychologist-guided online therapies, application-based online interventions, and chat counseling. Discussion Public knowledge of online psychological intervention is quite adequate. However, there are still a number of issues that the community doesn't understand, such as intervention design and understanding regarding the effectiveness of online psychological intervention. Nonetheless, people's intention to use psychological intervention is increasing in line with the challenges during the Covid-19 pandemic, which required people to use digital technology in their daily lives. Furthermore, efforts are needed to provide public understanding regarding the use of online psychological intervention. Conclusion The community has sufficient knowledge and interest in online psychology services. There is a positive relationship between knowledge and intention to use online psychological interventions. Education is needed to increase public understanding regarding online interventions. Keywords: telepsychology, online interventions, mental health